How to run a great worshop : - Sims, Nikki Highmore (Pearson Prentice Hall, 2006)
This interactive guide is designed especially for busy managers - people whose main role is not training and will take you through a simple step-by-step process that results in stimulating, fun and effective workshops and presentations.Just some of the many scenarios the book will help you tackle include: * How to put together training session from scratch when you have 'blank page, blank face' syndrome here's the step-by-step solution * You've done some training but you aren't getting the desired results from your sessions here's what do to about it * You haven't time to write 80 sexy PowerPoint slides for a session you are running here's what to do instead that will be even more effective "and "take half the time * You're dreading the experience of being 'up the front' here's how to shift the onus from you to your participants